Low Pitched Voices Are Perceived as Masculine and Attractive but Do They Predict Semen Quality in Men? - Simmons, Leigh W.; Peters, Marianne; Rhodes, Gillian (PLOS ONE, 2011)
Women find masculinity in men's faces, bodies, and voices attractive, and women's preferences for men's masculine features are thought to be biological adaptations for finding a high quality mate. Fertility is an important aspect of mate quality. Here we test the phenotype-linked fertility hypothesis, which proposes that male secondary sexual characters are positively related to semen quality, allowing females to obtain direct benefits from mate choice. Specifically, we examined women's preferences for men's voice pitch, and its relationship with men's semen quality. Consistent with previous voice research, women judged lower pitched voices as more masculine and more attractive. However men with lower pitched voices did not have better semen quality. On the contrary, men whose voices were rated as more attractive tended to have lower concentrations of sperm in their ejaculate. These data are more consistent with a trade off between sperm production and male investment in competing for and attracting females, than with the phenotype-linked fertility hypothesis.